How to determine the pion cloud of the constituent quark - Baumgärtner, Stefan; Pirner, Hans J.; Königsmann, K.; Povh, Bogdan (Zeitschrift für Physik. A, Hadrons and nuclei, 1996)
We calculate the differential cross section for semi-inclusive pion production in electron proton reactions using a model where the physical quark fluctuates with some probability to quark plus pion. The kinematic regions for a determination of this ‘pion cloud’ are evaluated.
Gesehen am 05.03.2018